If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + -6) + -2x = 2x + 4 Reorder the terms: 2(-6 + 4x) + -2x = 2x + 4 (-6 * 2 + 4x * 2) + -2x = 2x + 4 (-12 + 8x) + -2x = 2x + 4 Combine like terms: 8x + -2x = 6x -12 + 6x = 2x + 4 Reorder the terms: -12 + 6x = 4 + 2x Solving -12 + 6x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + 6x + -2x = 4 + 2x + -2x Combine like terms: 6x + -2x = 4x -12 + 4x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + 4x = 4 + 0 -12 + 4x = 4 Add '12' to each side of the equation. -12 + 12 + 4x = 4 + 12 Combine like terms: -12 + 12 = 0 0 + 4x = 4 + 12 4x = 4 + 12 Combine like terms: 4 + 12 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| -5(y-3y)+5=-6(2y-y)+8+15y | | W=1925-550t | | -4x-2=7x+42 | | X-2+4=6+4-x | | -5(y-3y)=-6(2y-y)+8+15y | | 3/13=v/7 | | 5[5m-(m+4)]=-8m+16 | | 3x^3-3x^2+90x=0 | | 1/5fk | | 10x-2=20x+18 | | 2(x+6)3=x-5 | | f(x)=5r-1 | | 8x-22=60+6x | | 7(a-6)+11=4(a-4) | | (3x^1)/(y^-1) | | -p^2-11p=0is | | 5-12x=-43 | | 34*m-1/3=1/2 | | f(x)=567 | | 3a^3+3ab^2+5a^2b+5b^3= | | 4+3n=6-5(n-2) | | 17-3n=27 | | -2m-2+m=-0.4(5m+20) | | 35/1000=x | | 4+b=-3(3b+2) | | 35=.5(3)(7+b) | | 1000-35=x | | 20-13=3x | | 11x+35=1000 | | -5h+2=-4(h-1) | | 1000x-35=x | | 1000-35x=x |